Africa holds weak and strong cards: to deal with the challenges of poverty on the continent - Nicol, Martin (New Agenda: SA Journal of Social and Economic Policy, 2024)
Twenty-five years ago, as a not-so-young economist, I worked as a diplomat for South Africa to promote trade and investment with Canada and the UK. We did not often meet with our African counterparts, as we were competitors, all trying to win over the same foreign investors and purchasers of our exports. In any event South Africa was not popular. It did not even get support from the rest of Africa when it bid to host the 2004 Olympic Games in Cape Town. One exception was in 2000, when Canada organised “Africa Direct” – a week-long early example of an “Africa plus one” event where a rich country (such as Japan,1 China,2 Russia, even Italy3) calls for an economic or diplomatic meeting with “Africa” (see Usman, 2023; Soule, 2021). The rich country sets the agenda and chooses the venue, and all the African delegations come, cap in hand.